Self-Conscious or Fear of Hurting Another’s Feeling? An Experimental Investigation on Promise-Keeping - Zhang, Wenjie; Zhu, Xianchen; Guan, Hongyu; Li, Tao (Frontiers in Psychology, 2020)
We conducted an experimental investigation into whether the effect of nonbinding verbal promises in enhancing cooperation among promisors is derived from the internalized norm mechanism or the expectation-based mechanism. We proposed a new experimental design based on the standard trust game to separate the two possible influence mechanisms of promises and assess the empirical support for these two mechanisms for the effect of promises. We also identified individuals’ cooperation preferences to further investigate whether the effect of promises and its underlying mechanism differ between individuals with different preferences. The results show that promises significantly improve promisors’ cooperation level, and this effect is only in line with the internalized norm mechanism rather than with the expectation-based mechanism. Additionally, the introduction of nonbinding promises has different impacts on the behavior of selfish individuals and conditional cooperators, but both sets of the impacts can be interpreted as evidence for the internalized norm mechanism, while neither is supportive of the expectation-based mechanism. This paper provides empirical evidence consistent with the internalized norm mechanism for the effect of promises in promoting cooperation. There appears to be no support for the expectation-based mechanism.